PROCEDURE FOR FORMATION OF DATA FILE ON THE COMPUTERIZED SYSTEM THE NAVY SHIP OPERATIONS - Sapto Haryono; Aqwam Rosadi Kardian,S.kom.,MMSI (Jurnal Sistem Informasi, 1997)
In the computerized data of this Navy ship operations in which the formation of the file is a very important part to establish reporting systems are conducted periodically. For that needed proper preparation of files in order to support the system and able to accommodate any required data elements.Â  These data are stored in files must be able to provide comprehensive information to the users as well as the heads of the Navy in any decision made or capable of providing information to personnel who require the operation of the fleet.